Pemakaian Bentuk Ringkas dalam Wacana Jual Beli - Atiqa Sabardila; Hari Kusmanto; Irfan Hidayah (Madah: Jurnal Bahasa dan Sastra, 2019)
The meeting of people from different linguistic backgrounds in a speech event can bring up unique language variations because at least two different languages are involved. This study aims to identify the use of concise forms in the discourse of buying and selling shoes and cloth in Pasar Benteng, Surakarta City. The data in this study are in the form of words, phrases, clauses, and sentences. The data source is the speech of shoes and fabric traders at Pasar Benteng. The data collection used is the method of listening or listening with advanced techniques in the form of a competent free trial (TSBLC). The methods are used to analyze the data in this study are (1) mark-reading method; (2) referential methods; (3) pragmatic method; (4) extending techniques; and (5) insert technique. The results show that there were three concise forms in the discourse of buying and selling shoes and cloth in Benteng Market, namely: (1) the concise form in the form of words (a) by obscuring phonemes, (b) by melting syllables; (2) the concise form in the form of clause; and (3) the concise form of sentence. This shows the use of language in the discourse of buying and selling by using a variety of non-formal languages. The use of the concise form is a convention between traders and buyers.